Decomposition and nitrogen mineralization of individual and mixed maize and soybean residue - Gezahegn, Almaz Meseret; Abd Halim, Mohd Ridzwan; Mohammad Yusoff, Martini; Abd. Wahid, Samsuri (MAYFEB Technology Development, 2016)
An increased knowledge of crop residue decomposition and nutrient release pattern is a critical component for nutrient cycling in low-input production systems. An incubation laboratory experiment was carried out to determine decomposition rate and N mineralization of individual and mixed maize and soybean residue. The experiment was carried out in randomized complete design (CBD) with three replications. The treatments consisted of maize, soybean and maize + soybean residue and control (without residue). The result showed that the C mineralization was significantly greater in crop residue amended soils compared to that of control (unamended) soil. The rate of decomposition of crop residue was highly influenced by the C:N ratio and the composition of the cell wall particularly the lignin content. The residues containing soybean had a faster rate of decomposition and released higher N compared to maize residues. At the end of the incubation study, the percentage of the added C decomposition was as follows: Soybean residue (66%) > mixture of maize and soybean residue (56%) > maize residue (46%). Net N mineralization in soils were occurred with soybean (7.4 to 98.4 mg/kg soil) and maize + soybean residue (4.7 to 67.9 mg/kg soil) throughout the study, whereas maize residue was characterized by N immobilization (-10.75 to -3.69 mg/kg soil) until 60 days. Therefore, it can be conclude that residue containing soybean can be a potential sources of mineral N.